2018
DOI: 10.24925/turjaf.v6i6.642-651.1415
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of microbiological and residual antibiotics status in milk sold in Abeokuta, Ogun State. Nigeria

Abstract: This study investigated the prevalence and concentration of antibiotic residues in twenty brands of milk. Determination and quantification of antibiotic residues was done using High Performance Liquid Chromatography. Aerobic plate count was carried out and the associated bacteria isolated. Identification of bacteria was done using standard microbiological methods. Molecular characterization and identification of bacterial isolates was done using 16S rRNA gene sequencing method. Antibiotic sensitivity was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…These two behaviours were reported by the majority of the dairy farmers surveyed. In Benin and in West Africa, several studies showed that milk usually contains antibiotic residues, particularly tetracyclines, beta-lactams, aminoglycosides, penicillin, sulphonamides, and macrolides (Madougou et al 2019;Mensah et al 2019;Oluwafemi et al 2018;Olatoye et al 2016;Bagré et al 2015;Mensah et al 2014;Addo et al 2011). Therefore, J o u r n a l P r e -p r o o f 16 dairy farmers should be trained to the use of good hygiene and husbandry practices according to the legislation recommendation.…”
Section: Potential Sources Of Wagashi Gassirè Contaminationmentioning
confidence: 99%
“…These two behaviours were reported by the majority of the dairy farmers surveyed. In Benin and in West Africa, several studies showed that milk usually contains antibiotic residues, particularly tetracyclines, beta-lactams, aminoglycosides, penicillin, sulphonamides, and macrolides (Madougou et al 2019;Mensah et al 2019;Oluwafemi et al 2018;Olatoye et al 2016;Bagré et al 2015;Mensah et al 2014;Addo et al 2011). Therefore, J o u r n a l P r e -p r o o f 16 dairy farmers should be trained to the use of good hygiene and husbandry practices according to the legislation recommendation.…”
Section: Potential Sources Of Wagashi Gassirè Contaminationmentioning
confidence: 99%
“…These two behaviours were reported by the majority of the dairy farmers surveyed. In Benin and in West Africa, several studies showed that milk usually contains antibiotic residues, particularly tetracyclines, beta-lactams, aminoglycosides, penicillin, sulphonamides, and macrolides (Madougou et al, 2019;Mensah et al 2014bMensah et al , 2019Oluwafemi et al, 2018;Olatoye et al, 2016;Bagr e et al, 2015;Addo et al, 2011). Therefore, dairy farmers should be trained to the use of good hygiene and husbandry practices according to the legislation recommendation.…”
Section: Potential Sources Of Wagashi Gassir E Contaminationmentioning
confidence: 99%